Migration and urbanization in Ucayali region: 1981-2007 - Diaz Encinas, Alida (2009)
The purpose of this study is to analyze the processes of migration and urbanization over time (1981-2007) in the Ucayali region and the socio demographic and economic impact of migrants, these are looking for opportunities, in order to increase their income and improve their standard of living. Ucayali region is a recipient of migrants with positive net migration. Pucallpa, capital of the region is a focus of attraction for immigrants arriving from the provinces, districts and villages and the surrounding departments, so much so that is facing problems of infrastructure and basic needs of migrant and native population.